A-ONE: HIGH YIELDING, CLCV TOLERANT AND TRANSGENIC BT. COTTON VARIETY FOR IRRIGATED AREAS OF PAKISTAN - S. B. Hussain; Z. Ali; H. N. Khan (Journal of Animal and Plant Sciences, 2014)
Allah Din One (A-One) has been bred through hybridization of a local commercial cotton variety FVH-53 and an exotic variety SL-223 containing Cry1 Ac Gene MON-531 event. Cross was attempted during 2001 under green house conditions at Allah Din Research Centre, Bahaudin Zakariya University, Multan. The strain was bulked during early 2005 in F7th generation. All developmental work of A-One had been completed before promulgation of National Bio-Safety rules, 2005. After completion of all Micro, Varietals and Zonal Varietals trials, A-One was tested for two consecutive years 2010-12 for various preliminary yield, disease, lint characters and confirmation of Bt Gene by Distinctness, Uniformity and Stability test, Punjab Seed Corporation yield test and National Coordinated Bt. Trial (NCBT). On the bases of over all good performance, A-One was approved by Provincial Seed Council, Punjab and registered by FSC & RD, Islamabad for general cultivation in 2011-12. The optimum sowing time of A-One is 1st May to 15th May and 1st week of March for early sowing. The development of A-One strengthened the much needed gene pool for Bt Cotton in the country.
Keywords: Bt cotton; Variety development; high yielding